Case Report: Pleuropulmonary Blastoma in a 2.5-Year-Old Boy: 18F-FDG PET/CT Findings - Ruan, Dan; Sun, Long (Frontiers in Nuclear Medicine, 2021)
Pleuropulmonary blastoma (PPB) is a rare invasive primary malignancy in the thoracic cavity that occurs mainly in infants and children. It is often misdiagnosed and not treated correctly and promptly due to the lack of specificity of clinical symptoms and conventional imaging presentations. We report a 2.5-year-old boy who underwent X-ray chest radiography, chest CT, and 18F-FDG PET/CT. PET/CT images demonstrated a sizeable cystic-solid glucose metabolism heterogeneous mass in the left thoracic cavity. The diagnosis of PPB (type II) was finally confirmed by a CT-guided puncture biopsy of the active tumor tissue. This case highlights the critical role of PET/CT in the diagnosis of PPB in children.